Refleksje nad rozwojem badań i kształcenia w zakresie logistyki - Kurowski, Lech (Perspectives for Research and Training in Logistics, 2005)
The paper studies dynamic growth of demand for logistic services and their growing role in national economies. Logistics research and training follow that trend to satisfy market demand for adequately trained personnel.Consequently a question arises on limits to this process, or for how long would the logistic services grow faster than the rest of the economy? Two on-going processes determine fast growth of logistic services - the search for improved microeconomic efficiency and the deepening of specialization and globalization processes in international markets. Both processes, as yet, are far from being completed. In the coming years, consequently one can expect a sustained high growth of demand for logistic services in different innovative forms, sometimes yet to be developed. A particular role could be played by networking that should provide the highest level of reliability of service for all the users. Consequently there is a role to play for the research. However dynamic growth of logistics related training might be coming to an end due to gradual saturation of the demand for university trained logisticians. The demand for future training might therefore concentrate on skills upgrading rather than follow the existing curricula.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1078, s. 81-89